2007
DOI: 10.1021/cb700012y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Structural Basis of Stereospecific Cβ-Hydroxylation in Calcium-Dependent Antibiotic, a Daptomycin-Type Lipopeptide

Abstract: Non-ribosomally synthesized lipopeptide antibiotics of the daptomycin type are known to contain unnatural beta-modified amino acids, which are essential for bioactivity. Here we present the biochemical and structural basis for the incorporation of 3-hydroxyasparagine at position 9 in the 11-residue acidic lipopeptide lactone calcium-dependent antibiotic (CDA). Direct hydroxylation of l-asparagine by AsnO, a non-heme Fe(2+)/alpha-ketoglutarate-dependent oxygenase encoded by the CDA biosynthesis gene cluster, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
138
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(145 citation statements)
references
References 46 publications
6
138
0
1
Order By: Relevance
“…Natural peptides often incorporate hydroxylated amino acids. 16,17,19,20 In chromophore biosynthesis, the producing strains utilize similar b-hydroxylation system consisting of cytochrome P-450, non-ribosomal peptide synthetase, and discrete thioesterase for conversion of L-tryptophan to 3. 16,17 Chromophore biosynthetic clusters for 1 and 2 consist of genes encoding enzymes for tryptophan metabolism, such as kynurenic acid 21 acid, 22,23 which are presumably different from the constitutive enzymes (Scheme 2).…”
Section: Cloning Expression and Purification Of Swb1 And Swb2mentioning
confidence: 99%
“…Natural peptides often incorporate hydroxylated amino acids. 16,17,19,20 In chromophore biosynthesis, the producing strains utilize similar b-hydroxylation system consisting of cytochrome P-450, non-ribosomal peptide synthetase, and discrete thioesterase for conversion of L-tryptophan to 3. 16,17 Chromophore biosynthetic clusters for 1 and 2 consist of genes encoding enzymes for tryptophan metabolism, such as kynurenic acid 21 acid, 22,23 which are presumably different from the constitutive enzymes (Scheme 2).…”
Section: Cloning Expression and Purification Of Swb1 And Swb2mentioning
confidence: 99%
“…The study by Strieker et al 27 have shown that AsnO converts the free L-Asn to L-hAsn before incorporation into the growing peptide. According to their model, L-hAsn binds to the adenylation (A)-domain of the CA hAsn9 TE module of CdaPS2, in which it is converted to D-hAsn and incorporated into the growing peptide chain.…”
Section: Discussionmentioning
confidence: 99%
“…The AsnO protein was crystallized, and the catalytic binding pocket for L-Asn has been defined as a 10 letter code: EQNHENDHR at positions 125, 144, 146, 155, 157, 158, 241, 287 and 305. 27 The LptL protein has an identical L-Asn catalytic binding pocket displaced by eight amino acids relative to AsnO, and starting at position E117. Therefore, even though the lptL and asnO genes and their protein products have diverged considerably (47% identical amino acids), they have conserved the L-Asn binding pocket 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that within the avilamycin biosynthetic cluster in Streptomyces viridochromogenes, a set of putative α-ketoglutarate, nonheme iron-dependent [AKG/Fe(II)-dependent] oxygenases may be capable of catalyzing both orthoester linkage and methylenedioxy bridge formation (9,10). AKG/Fe(II)-dependent oxygenases are powerful oxidants that catalyze a range of reactions, including oxidative cyclizations, hydroxylations, peroxidations, epoxidations, desaturations, and halogenations (11)(12)(13)(14). This reactivity is suited to orthoester linkage and methylenedioxy bridge biosynthesis.…”
mentioning
confidence: 99%